Advanced supramolecular nanoarchitectonics - Ariga, Katsuhiko, 1962-; Aono, Masakazu (Micro & nano technologies., 2019)
Advanced Supramolecular Nanoarchitectonics provides the latest information on design at the nanoscale, presenting a range of the new challenges that arise when the manipulation techniques that work at the macro- and micro-scale do not work at the nanoscale. Nanoarchitectonics approaches material design via a profound understanding of the interactions between individual nanostructures and their organization. This book presents the more advanced features of this research paradigm, focusing on the materials fabrication of self-defined nanostructures and demonstrating possible applications of these fabricated materials.